Dyadic Violence and Readiness to Change among Male Intimate Partner Violence Offenders - Crane, Cory A. (Crim Behav Ment Health, 2015)
BACKGROUND: Although readiness to change is associated with mandated partner violence treatment compliance and subsequent violent behavior among male offenders (e.g., Eckhardt et al., 2004; Scott & Wolfe, 2003), our understanding of the factors associated with pretreatment change remains limited. Offender research indicates that individual and dyadic violent behavior are highly variable and that such variability may provide insight into levels of pretreatment change (Archer, 2002; Holtzworth-Monroe & Stuart, 1994). AIMS/HYPOTHESES: We sought to examine the associations between indicators of change and individual as well as dyadic violence frequency in a sample of male partner violence offenders. METHOD: To determine whether severity and perceived concordance in the use of violence among male offenders and their female partners influenced readiness to change at pretreatment, 82 recently adjudicated male perpetrators of intimate partner violence were recruited into the current study and administered measures of readiness to change violent behavior (Revised Safe at Home Scale; Begun et al., 2008) as well as partner violence experiences (Revised Conflict Tactics Scale; Straus et al., 1996). RESULTS: Analyses revealed an interaction between offender-reported male and female violence in the prediction of pretreatment readiness to change such that greater male violence was associated with greater readiness to change among males who reported that their female partners perpetrated low, but not high, levels of violence. Consistently, greater female violence was associated with lower readiness to change only among the most violent male offenders. CONCLUSIONS AND IMPLICATIONS FOR CLINICAL PRACTICE: Results provide support for the assertion that the most violent offenders may be the most resistant to partner violence intervention efforts, particularly when they perceive themselves to be victims as well. Enhanced motivational and couples programming may facilitate treatment engagement among the high-risk group of male offenders who report concordant relationship violence.